EDUKASI KESEHATAN TENTANG PENCEGAHAN STUNTING PADA IBU BAYI USIA 0-12 BULAN - Nurul Kaamilah; Miftah Fitriyani; Pipin Nurlinda (MAJU : Indonesian Journal of Community Empowerment, 2026)
Stunting is a nutritional problem that remains a challenge in improving the quality of child health in Indonesia. Mothers' low knowledge about stunting prevention is one of the factors contributing to the incidence of stunting in children. This community service activity aims to increase the knowledge of mothers of infants aged 0–12 months about stunting prevention through health education using booklets in Sungai Beliung Village, Pontianak City. The method used was health education through counseling and interactive discussions using booklets. Participants' knowledge was measured before and after the education to assess the effectiveness of the activity. The results showed an increase in participants' knowledge after receiving education, indicated by an increase in the number of participants with good knowledge. The booklets helped participants understand information about stunting, the importance of the First 1,000 Days of Life, meeting children's nutritional needs, and growth monitoring. Health education using booklets effectively increases mothers' knowledge and has the potential to support stunting prevention efforts in the community.